Inclusion health concepts in our Arabic textbooks for the first three grades in Jordan - Alzalabeih, Mahmoud Mohammed Freij (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the degree of inclusion of health concepts in the books of Arabic language for the first three grades in Jordan. To achieve this, the researcher analyzed the content of Arabic language books. The study used the descriptive analytical method, The study tool was developed for this purpose, where it classified the categories of health concepts into five main areas: (physical health, healthy nutrition, environmental health, psychosocial health, disease and prevention). The reliability and validity of the used tool were verified.The results showed that our Arabic language book for the third basic grade ranked first in the total number of iterations that total (366) iterations As the share of the book for the third basic class reached (171) repetitions, and after it came the book for the second basic class, when it reached (102) repetitions, and after it came the book of the primary first grade (93) repetitions. The study recommended that Our Arabic language books for grades (first, second, and third) include health concepts that came in low rates or did not have any repetition, such as concepts of non-communicable diseases, methods of disease transmission, avoiding violence, and air pollution and further studies be conducted to identify health concepts in books and other academic stages.
Keywords: content analysis; health concepts; books for our Arabic language; The first three rows